Acylated anthocyanins from organic purple-fleshed sweet potato (Ipomoea batatas (L.) Lam) produced in Brazil (Scientia Agricola, 2021)
Acylated anthocyanins from a purple-fleshed sweet potato (PFSP), obtained by organic cultivation in Brazil, were characterized after separation by a high performance liquid chromatography-diode array detector (HPLC-PDA). These anthocyanins were manually collected at the detector output, concentrated and injected into a high resolution mass spectrometer (ESIQTOF-MS2). Twenty-two acylated anthocyanins were detected. Among them, sixteen had been reported in the literature and six, derived from peonidin were reported for the first time in sweet potato roots in this study. These compounds showed molecular ions with accurate mass/charge ratios (m/z) of 909.2081, 961.3010, 961.2571, 963.3345, 1123.2932 and 1179.3862. Although anthocyanins in PFSP have already been extensively studied, the variety studied in this work is probably genetically different from all varieties and cultivars already researched, which would explain why these anthocyanins have not been observed in the previously studied varieties.